Cost-effective IoT-based automated vehicle headlight control system: design and implementation - Begum, Momotaz; Ullah, Nayeem; Shuvo, Mehedi Hasan; Islam, Towhidul; Hossen, Thofazzol; Uddin, Jia (Institute of Advanced Engineering and Science, 2025)
The current world would be difficult without vehicles, which offer vital advantages for social connectivity, mobility, and technical advancement. Though motor vehicles provide benefits to passenger transportation, they also present certain challenges in their use. A major issue is nighttime traffic accidents caused by headlamps from automobiles traveling in reverse directions, that's why there is a high probability of accidents due to the glare on the driver's eyes. The phrase